Bowel obstruction and perforation secondary to barbed suture after minimally invasive inguinal hernia repair: report of two cases and literature review - Liming Wang; Taku Maejima; Susumu Fukahori; Shoji Nishihara; Daitaro Yoshikawa; Toru Kono (Surgical Case Reports, 2021)
Abstract Background Laparoscopic transabdominal preperitoneal patch (TAPP) is now commonly used in the repair of inguinal hernia. Barbed suture can be a fast and effective method of peritoneal closure. We report two rare cases of small bowel obstruction and perforation caused by barbed suture after TAPP. Cases Patient 1 is a 45-year-old man who underwent laparoscopic repair of a right inguinal hernia. Barbed suture was used to close the peritoneal defect. At 47 days after the operation, he was diagnosed with a small bowel obstruction caused by an elongated tail of the barbed suture. Emergency laparoscopic exploration was performed for removal of the embedded suture and detorsion of the volvulus. The second patient is a 50-year-old man who was admitted with a small bowel perforation one week after TAPP herniorrhaphy. Emergency exploration revealed that the tail of the barbed suture had pierced the small intestine, causing a tiny perforation. After cutting and releasing the redundant tail of the barbed suture, the serosal and muscular defect was closed with 2 absorbable single-knot sutures. Both patients have recovered well. Finally, we searched the PubMed database and reviewed the literature on the effectiveness and safety of barbed suture for TAPP. Conclusions Surgeons should understand the characteristics of barbed suture and master the technique of peritoneum closure during TAPP in order to reduce the risk of bowel obstruction and perforation.